The Role Of The Principles Of Civil Procedural Law In Ensuring A Fair Trial - Akhmedov Jamoliddin Davronovich (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2026)
The article examines the role of the principles of civil procedural law in ensuring a fair trial as one of the key elements of the right to judicial protection. The essence, content, and significance of the fundamental principles of civil procedure – such as legality, judicial independence, adversarial proceedings and equality of the parties, publicity, dispositiveness, and procedural economy—are analyzed. Particular attention is paid to their functional role in shaping a fair, transparent, and effective procedure for the consideration of civil cases. Based on an analysis of procedural legislation and judicial practice, it is substantiated that the principles of civil procedural law serve as system-forming foundations that ensure a balance between public and private interests, equality of participants in the proceedings, and protection of their rights and legitimate interests. The article concludes that the consistent and comprehensive implementation of the principles of civil procedure is a necessary condition for enhancing public confidence in the judiciary and improving the effectiveness of justice.